Finding food: Issues and challenges in using Geographic Information Systems (GIS) to measure food access - Ann Forsyth; Leslie Lytle; David Van Riper (Journal of Transport and Land Use)
A significant amount of travel is to find food. This paper examines challenges in measuring access to food using GIS, of importance in studies of both travel and eating behavior. It compares different sources of data available including fieldwork, land use and parcel data, licensing information, commercial listings, taxation data, and online street-level photographs. It proposes how to classify different kinds of food sales places in a way that says something about their potential for delivering healthy food options. Analysts need to clearly conceptualize key variables, document measurement processes, and be clear about the strengths and weaknesses of data.